2022
DOI: 10.1039/d2ra02518c
|View full text |Cite
|
Sign up to set email alerts
|

Study on low-temperature cycle failure mechanism of a ternary lithium ion battery

Abstract: The failure of low-temperature performance of ternary lithium-ion battery is the result of side reactions such as lithium deposition, positive material transition metal ion dissolution and electrolyte decomposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…However, the performance of some new energy technologies in the low-temperature environment is not ideal, in this state, the battery shows that the electrode material is constantly deactivated, the battery capacity loss increases, and the charging rate slows down [10]. According to the existing experimental research, by comparing the lithium titanate and ternary materials in -10 ℃ cycle times and discharge capacity relationship, found that ternary batteries in the low-temperature cycling discharge capacity first increased and then slowed down in two phases, and from the experiments concluded that the lithium ions in the negative end of the precipitation of the battery in the low-temperature conditions is a key factor that affects the battery in low-temperature conditions function functionally stable or not, the battery safety performance degradation or not [16]. Therefore, it is necessary to find more suitable electrode materials for use in low-temperature environments to promote the development and application of new energy technologies.…”
Section: Low Temperature Conditionsmentioning
confidence: 98%
“…However, the performance of some new energy technologies in the low-temperature environment is not ideal, in this state, the battery shows that the electrode material is constantly deactivated, the battery capacity loss increases, and the charging rate slows down [10]. According to the existing experimental research, by comparing the lithium titanate and ternary materials in -10 ℃ cycle times and discharge capacity relationship, found that ternary batteries in the low-temperature cycling discharge capacity first increased and then slowed down in two phases, and from the experiments concluded that the lithium ions in the negative end of the precipitation of the battery in the low-temperature conditions is a key factor that affects the battery in low-temperature conditions function functionally stable or not, the battery safety performance degradation or not [16]. Therefore, it is necessary to find more suitable electrode materials for use in low-temperature environments to promote the development and application of new energy technologies.…”
Section: Low Temperature Conditionsmentioning
confidence: 98%
“…[ 5 ] To ensure the safety of LIBs, it is unavoidable to understand and analyze the phenomena and causes of battery failure. [ 6 ] The commonly found failure phenomena include poor electrolyte wetting, [ 7 ] cell expansion, [ 8 ] gas production inside the cell, [ 9 ] lithium dendrites generation, [ 10 ] solid electrolyte cracking, [ 11 ] etc. [ 12 ] The causes of each phenomenon are different and some of them are unavoidable, but only by analyzing and correcting them as much as possible can we guarantee the safety of the battery.…”
Section: Introductionmentioning
confidence: 99%